2019
DOI: 10.1103/physreve.99.053301
|View full text |Cite
|
Sign up to set email alerts
|

Generalized lattice Boltzmann model for frosting

Abstract: Frosting is a multiscale and multiphysics problem, which presents a significant challenge for numerical methods. In this study, a generalized lattice Boltzmann (LB) model is developed to simulate the frosting of humid air at representative elementary volume scale. In this model, three LB equations are introduced to describe the evolution of distribution functions for velocity, temperature, and humidity (i.e., mass fraction of water vapor in the humid air) fields, respectively. The frost layer is regarded as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…We perform numerical simulations based on a two-species lattice Boltzmann (LB) model, with suitable pseudo-potential interactions. Recently, the LB method has become a very efficient and powerful simulation method for complex flows [29][30][31][32][33][34][35][36][37][38][39][40] . The LB equation takes the form [41][42][43][44] :…”
Section: Model Description and Validationmentioning
confidence: 99%
“…We perform numerical simulations based on a two-species lattice Boltzmann (LB) model, with suitable pseudo-potential interactions. Recently, the LB method has become a very efficient and powerful simulation method for complex flows [29][30][31][32][33][34][35][36][37][38][39][40] . The LB equation takes the form [41][42][43][44] :…”
Section: Model Description and Validationmentioning
confidence: 99%
“…The above evolution equation scheme with B is widely applied in the liquid-solid phase change simulations with the LB model [21][22][23][24][25][26][27][28]. In these works, the solid density equals the liquid one.…”
Section: Solid-liquid Phase Change With Volume Changementioning
confidence: 99%
“…In these works, the LBM enables nontracking of the interface and the coupled equation of state (EOS) to adjust the separation of vapor and liquid phases according to the local state parameters. Several enthalpy-based LB models were also developed to deal with the solidification (or freezing) and melting processes [21][22][23]. To our best knowledge, no study has been reported using LBM for simulating the water freezing phenomenon with volume expansion or density change.…”
Section: Introductionmentioning
confidence: 99%
“…As a powerful pore-scale solver, the lattice Boltzmann (LB) method has been applied widely to study complex fluid flows in porous structures over the past three decades (Li et al 2016;Lei, Luo & Wu 2019;Lei & Luo 2021a;Chen et al 2022). Accordingly, LB simulations were reported to investigate separately the physical processes that are encountered in CO 2 desublimation, including the unsteady fluid flow, the heat and mass transfer, and the active gas-solid interface for desublimation.…”
Section: Introductionmentioning
confidence: 99%
“…As a powerful pore-scale solver, the lattice Boltzmann (LB) method has been applied widely to study complex fluid flows in porous structures over the past three decades (Li et al. 2016; Lei, Luo & Wu 2019; Lei & Luo 2021 a ; Chen et al. 2022).…”
Section: Introductionmentioning
confidence: 99%